Effective retirement age from employment and full‐time employment, and the impact of the 2008 crisis. (29th April 2019) - Latulippe, Denis; Fontaine, Florence
Abstract: Estimates of effective retirement age based on labour force participation rates are commonly used for actuarial experience review and policy development. However, the transition from work to retirement and the socio‐economic environment have evolved over the years, influenced by a growing role for gradual retirement and the labour market impact of the 2008 economic crisis. Rather than focusing exclusively on retirement ages based on labour force participation rates, this article presents complementary estimates of retirement ages to better assess the effective retirement age from employment. It also introduces the concept of retirement from full‐time employment, showing that the retirement age from full‐time employment is systematically lower than the retirement age from employment. The results reveal that the trend towards an increase in the retirement age has been impacted by economic conditions when considering the effective employment of older workers. Results are presented for different Member countries of the Organisation for Economic Co‐operation and Development over the period 2005–2015.